Effects of glibornuride versus metformin on eye lenses and skin in experimental diabetes - (:unkn) unknown (GEORG THIEME VERLAG KG, 2006)
The aim of the study was to investigate the effect of glibornuride (CAS 26944-48-9) and metformin (CAS 657-24-9) on eye lenses and skin of streptozotocin (STZ)induced diabetic rats. The drugs were administered daily to one diabetic and one control group separately from day 14 to day 42. After 42 days, diabetes caused significant increases in blood glucose levels, non-enzymatic glycosylation (NEG) of skin and lens proteins and skin lipid peroxidation (LPO) levels as well as decreases in body weights and lens glutathione (GSH) levels. Metformin administration to the diabetic rats produced more significant reduction in blood glucose than glibornuride. Metformin produced non-significant increase in NEG levels in lenses and skin. Unlike metformin, glibornuride increased NEG levels significantly in lenses. Both drugs produced non-significant increase in lens GSH levels and decreases in skin LPO levels in diabetic rats. Sodium dodecyl sulphate (SDS) polyacrylamid gel electrophoresis revealed no significant difference in any of the protein bands between any of the groups. These observations suggest that metformin and glibornuride as oral antidiabetics have similar protective effects on tissues in STZ induced diabetic rats.
Keywords: antidiabetic drugs; CAS 657-24-9; CAS 26944-48-9; diabetes mellitus, eye lens, skin, tissue protection; glibornuride; metformin; PHARMACOLOGICAL-PROPERTIES